Contexto climático y parámetros meteorológicos en la parroquia Manuel Quiroga, Manabí - Ecuador - Loor Cantos, Diana Isabel (2025)
The objective of this research was to evaluate the climatic context and meteorological parameters in the Manuel Quiroga parish, in the province of Manabí, Ecuador. The methodology was structured through multiple phases, including the application of the Whittaker diagram from 1981 to 2022 to classify the prevailing climate in the studied area, the use of the HADCM3 climate projection model based on the SRES A1B, B1, and A2 scenarios, the Pearson correlation coefficient for the parameters recorded between July 2023 and July 2024, and bibliographic techniques aimed at collecting and analyzing meteorological information. As a result of the analysis, a tropical climate with a tendency towards arid conditions was identified, characterized by historical temperatures ranging between 25°C and 30°C. An average temperature increase was projected for the year 2100, with values of 1.72°C in the A1B scenario, 1.87°C in the A2 scenario, and 1.21°C in the B1 scenario. Regarding precipitation, the maximum estimated values were 337.40 mm, 328.23 mm, and 306.58 mm for the A1B, A2, and B1 scenarios, respectively. The variables with the highest correlation were solar radiation and UV index (0.97), temperature and UV index (0.88), as well as humidity and rainfall with 0.69 (medium-high). Finally, based on the results, a strategy guide was developed to prevent, mitigate, and adapt to the climatic context, strengthening the resilience of the inhabitants of the parish.